Integrated Circuit Authentication Hardware Trojans and Counterfeit Detection - Tehranipoor, Mohammad (Springer International Publishing : Imprint: Springer, 2014)
This book provides readers with a comprehensive introduction to hardware Trojans.  The authors explain the hardware Trojan taxonomy in detail, while delivering deep understanding of the potential impacts throughout the integrated circuit (IC) lifecycle. While discussing the shortcomings of current, industrial IC testing techniques for hardware Trojans, the authors describe the details of emerging techniques to detect them and to prevent their insertion into products.   ·         Provides a comprehensive introduction to hardware Trojans and their potential impact on the integrated circuit lifecycle; ·         Equips designers with tools for identifying potential vulnerabilities throughout the design cycle and manufacturing; ·         Describes state-of-the-art techniques for hardware Trojan design, detection, and prevention; ·         Analyzes susceptibility at the behavioral-, gate-, layout-level to Trojan insertion.